Stabilized model reduction for nonlinear dynamical systems through a contractivity-preserving framework - Chaturantabut, Saifon (Zielona Góra: Uniwersytet Zielonogórski)
This work develops a technique for constructing a reduced-order system that not only has low computational complexity, but also maintains the stability of the original nonlinear dynamical system. The proposed framework is designed to preserve the contractivity of the vector field in the original system, which can further guarantee stability preservation, as well as provide an error bound for the approximated equilibrium solution of the resulting reduced system.
Keywords: model order reduction; contractivity; ordinary differential equations; partial differential equations; proper orthogonal decomposition; discrete empirical interpolation method